SUDDEN DEATH DUE TO INTRACRANIAL COLLOID CYST (Iraqi Journal of Medical Sciences, 2016)
Intracranial colloid cysts are non-neoplastic epithelium-lined cysts of the central nervous system that almost always arise from the anterior third ventricle roof (immediately posterior to the foramen of Monro). These epithelium-lined, mucin-containg cysts can be found in asymptomatic patients; however, depending on their location, size, and degree of cerebrospinal fluid obstruction, patients may present with a variety of neurological symptoms. These symptoms can range from headaches to sudden death on rare occasions when there is acute hydrocephalus. This study describes a colloid cyst located between the two lateral ventricles at the level of foramen of Monro obstructing the cerebrospinal fluid (CSF) flow leading subsequently to sudden death and discovered incidentally during autopsy. The study was done in the Medico-legal institute in Baghdad from 1st of November 2012 to 1st of May 2013.Key words:Sudden Death, Colloid Cyst, Autopsy, Intracranium.
Keywords: Sudden Death; Colloid Cyst; Autopsy; Intracranium